Monitoring the levels of important nutrients in the food supply. (17th September 2013) - Neal, B.; Sacks, G.; Swinburn, B.; Vandevijvere, S.; Dunford, E.; Snowdon, W.; Webster, J.; Barquera, S.; Friel, S.; Hawkes, C.; Kelly, B.; Kumanyika, S.; et al.
Summary: A food supply that delivers energy‐dense products with high levels of salt, saturated fats and trans fats, in large portion sizes, is a major cause of non‐communicable diseases (NCDs). The highly processed foods produced by large food corporations are primary drivers of increases in consumption of these adverse nutrients. The objective of this paper is to present an approach to monitoring food composition that can both document the extent of the problem and underpin novel actions to address it. The monitoring approach seeks to systematically collect information on high‐level contextual factors influencing food composition and assess the energy density, salt, saturated fat, trans fats and portion sizes of highly processed foods for sale in retail outlets (with a focus on supermarkets and quick‐service restaurants). Regular surveys of food composition are proposed across geographies and over time using a pragmatic, standardized methodology. Surveys have already been undertaken in several high‐ and middle‐income countries, and the trends have been valuable in informing policy approaches. The purpose of collecting data is not to exhaustively document the composition of all foods in the food supply in each country, but rather to provide information to support governments, industry and communities to develop and enact strategies to curb food‐related NCDs.